(untitled) (Research, Society and Development, 2021)
Objectives: to investigate the occurrence of the nursing diagnosis of physical mobility impaired, its defining characteristics and related factors in patients with stroke in a public hospital. Method: documentary study on medical records of 40 patients admitted to the neurology sector with a diagnosis of stroke, between May and July 2020, with collection of sociodemographic data and related to the nursing process. Descriptive data analysis was used. Results: there was a predominance of males, the elderly, hypertensive patients, 50% of the medical records contained the nursing process, of which 17.5% had a nursing diagnosis of impaired physical mobility. The main related defining characteristics were: reduction in fine and gross motor skills and difficulty in turning around, as related factors, decreased muscle strength and altered cognitive function. Conclusion: the diagnosis of impaired physical mobility was not very significant and the defining characteristic was focused on the reduction of motor skills, related to decreased muscle strength.